Hydrophobicity and antioxidant activity acting together for the beneficial health properties of nordihydroguaiaretic acid - Paracatu, Luana Chiquetto [UNESP]; Quinello Gomes de Faria, Carolina Maria [UNESP]; Zeraik, Maria Luiza [UNESP]; Quinello, Camila; Renno, Camila; Palmeira, Patrcia; Fonseca, Luiz Marcos da [UNESP]; Ximenes, Valdecir Farias [UNESP] (Royal Soc Chemistry, 2015)
Nordihydroguaiaretic acid (NDGA) and rosmarinic acid (RA), phenolic compounds found in various plants and functional foods, have known antioxidant and anti-inflammatory properties. In the present study, we comparatively investigated the importance of hydrophobicity and oxidisability of NDGA and RA, regarding their antioxidant and pharmacological activities. Using a panel of cell-free antioxidant protocols, including electrochemical measurements, we demonstrated that the anti-radical capacities of RA and NDGA were similar. However, the relative capacity of NDGA as an inhibitor of NADPH oxidase (ex vivo assays) was significantly higher compared to RA. The inhibitory effect on NADPH oxidase was not related to simple scavengers of superoxide anions, as confirmed by oxygen consumption by the activated neutrophils. The higher hydrophobicity of NDGA was also a determinant for the higher efficacy of NDGA regarding the inhibition of the release of hypochlorous acid by PMA-activated neutrophil and cytokine (TNF-alpha and IL-10) production by Staphylococcus aureus-stimulated peripheral blood mononuclear cells. In conclusion, although there have been extensive studies about the pharmacological properties of NDGA, our study showed, for the first time, the importance not only of its antioxidant activity, but also its hydrophobicity as a crucial factor for pharmacological action.